Cogito Ergo Sum: Understanding the Professional Skepticism of Government Internal Auditors - Fatkhmol Risepdo; Erina Sudaryati (The Indonesian Accounting Review, 2025)
Descartes' philosophy, famous for the phrase "cogito ergo sum" (I think, therefore I am), emphasizes the importance of critical thinking and proper doubt to achieve truth. In the context of Government Internal Auditors (APIP), critical and objective thinking enables them to conduct independent assessments. This research reveals how APIP applies professional scepticism during audits, similar to Descartes' thought process. Both aim to find truth through critical thinking and proper doubt. By applying Descartes' principles, it is hoped that APIP's professional scepticism can be strengthened, contributing to further research.